Pengaruh Moderasi Dinamika Lingkungan pada Sistem Kontrol Akuntansi dan Kinerja Perusahaan - Muchamad Syafruddin (The Indonesian Journal of Accounting Research, 2013)
Contingency theory posits a strong relationship between accounting control system and organizational performance. In the past empirical studies, there were some contextual factors that moderating those relationship. The current study postulates and tests the moderating effect of environmental dynamism on the accounting control systems and performance nexus. The study finds that estimation result supports the hypothesis that there is moderating effect of environmental dynamism on the accounting control system and firm’s performance.